Moving images, Moving Methods: Advancing Documentary Film for Qualitative Research. (24th May 2021) - Borish, David; Cunsolo, Ashlee; Mauro, Ian; Dewey, Cate; Harper, Sherilee L.
With the widespread use of digital media as a tool for documentation, creation, preservation, and sharing of audio-visual content, new strategies are required to deal with this type of "data" for research and analysis purposes. This article describes and advances the methodological process of using documentary film as a strategy for qualitative inquiry. Insights are drawn from a multimedia study that explored Inuit-caribou relationships in Labrador, Canada, through the co-production of community-based, research-oriented, participatory documentary film work. Specifically, we outline: 1) the influence of documentary film on supporting the project conceptualization and collaboration with diverse groups of people; 2) the strength of conducting filmed interviews for in-depth data collection, while recognizing how place and activities are intimately connected to participant perspectives; and 3) a new and innovative analytical approach that uses video software to examine qualitative data, keep participants connected to their knowledge, and simultaneously work toward creating high impact storytelling outputs. The flexibility and capacity of documentary film to mobilize knowledge and intentionally create research outputs for specific target audiences is also discussed. Continued and future integration of documentary film into qualitative research is recommended for creatively enhancing our abilities to not only produce strong, rich, and dynamic research outputs, but also simultaneously to explore and communicate diverse knowledges, experiences, and stories.